Atmospheric and environmental impacts of volcanic particulates - Durant, AJ; Bonadonna, C; Horwell, CJ (Elements, 2010)
Volcanic emissions consist of a mixture of gases, aerosol, and silicate particles, which collectively span seven orders of magnitude in size. Airborne ash and sulfate aerosol in the lower atmosphere has short-lived atmospheric and climatic effects. Volcanic aerosol injected high into the stratosphere impacts atmospheric chemical cycles and the solar and terrestrial radiation budgets, and may influence climate over longer time-scales than aerosol particles in the lower atmosphere. Once at the surface, the impacts on local environments can be substantial through transport of halogens, trace metals, and metalloids, and subsequent leaching in aqueous solutions. Volcanic emissions may cause disruption to travel and aviation, and may damage surface infrastructure, potentially causing large economic losses.
EPrint Processing Status: Publisher does not permit full text to be deposited
Keywords: Volcanic ash; Aerosol; Particle; Sulfur dioxide; Volcano; Volcanic cloud; Climate; Atmosphere.